MANAJEMEN PEMBELAJARAN YANG MENYENANGKAN PADA MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) - PELANA, RAMDAN (JURNAL PENDIDIKAN DASAR, 2012)
Physical Education is essentially an integral part of a total sum education system aims to develop aspects of health, physical fitness, critical thinking skills, emotional stability, social skills, reasoning and moral action through physical activity and sport. Physical Education in the learning process, teachers are expected to teach a variety of sports basic movement skills, techniques and strategies of games and sports, internalization of values (sportsmanship, honesty, cooperation, etc.) and habituation of healthy living. In the lesson the teacher can provide a variety of approaches that students are motivated and keen to keep learning. To have the ability to manage learning (pedagogical) well, of course, teachers need to understand the important elements related to learning management.Keywords: Physical Education, Learning, Management, Fun